The Association between Spexin Levels, Lipid Profiles, Glucose Metabolism, and Immune Function in Newly Diagnosed Diabetes in Postmenopausal Iraqi Women (The Review of Diabetic Studies, 2024)
Background: Type 2 diabetes mellitus (TIIDM) is a metabolic disorder in which the level of glucose is elevated in the blood as a consequence of insulin resistance. Spexin (SPX) is a peptide involved in the regulation of blood glucose and lipid metabolism. Aims: The study aims were targeting the pathophysiology of TIIDM in postmenopausal women (PMW), where it focused on the evaluation of SPX levels in the serum of TIIDM-PMW. Results: There was a significant (P